(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
The present study was conducted in mortuary of Forensic medicine and toxicology department at Government medical college Vadodara during Jan-2013 to Dec-2016. We studied 220 excised hyoid bone from dead bodies of 110 male and 110 female for the fusion of Greater cornu of hyoid bone with body of hyoid bone in age group of 21 to 75 year. Mean age of unilateral fusion is 52.83 yr in male and 48.46yr in female. Mean age of Bilateral fusion is 62.78 yr in male and 60.17 yr in female. Throughout all age group fusion noted earlier in female sex. Overall mean age of unilateral fusion is 50.60yr and mean age of bilateral fusion is 61.30yr. There was significant association noted between fusion in the hyoid bone and advancing age. But still it cannot be considered a good indicator for estimating age as high degree variation noted in the age of fusion. In conclusion estimation of age by using hyoid bone is not reliable as time of fusion of greater cornu with the body of hyoid is irregular. But the present method can be a supplementary method for estimating age.